Comparative evaluation of abdominal hysterectomy by ligasure and conventional method - Singh, Harjinder; Jindal, Monika; Gupta, Monika; Goraya, S. P. S.; Behal, Manisha; ., Tanjeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the 2nd most common surgical procedure performed in women and is associated with various complications like any other major surgical procedure. The objectives and aims of this study was to compare the effects of ligasure and conventional clamping and suturing in abdominal hysterectomy. Methods: A randomized controlled trial was performed by randomizing the patients in 2 groups - ligasure (A) and conventional hysterectomy (B). Operative time, no. of sutures, blood loss, hospital stay and cost factor to patient were studied as its main outcomes. A total of 100 patients were studied. Results: 66% of patients in group A had duration of surgery that was less than an hour in spite of associated co-morbidities. More no (76%) of patients in Group A had significantly less blood loss (<50 ml) as compared to 60% of patients in Group B. Only one suture was used in 80% of patients in Group A while in group B all of the patients required more than one suture from stumps to vault. There by reducing the cost of surgery. Conclusion: Apparently ligasure group seems to have less time for surgery and less blood loss and more intraoperative and postoperative complications, but to prove one ligasure group superior or inferior over conventional method we need to have more studies. But yes, Ligasure group reduces the cost of surgery to patient by reducing suture consumption as compared to conventional group.